Effect of heparin on secondary brain injury in patients with subarachnoid hemorrhage: an additional 'H' therapy in vasospasm treatment. (2nd February 2017) - Bruder, Markus; Won, Sae-Yeon; Kashefiolasl, Sepide; Wagner, Marlies; Brawanski, Nina; Dinc, Nazife; Seifert, Volker; Konczalla, Juergen
Abstract : Objective: Secondary brain injury leads to high morbidity and mortality rates in patients with aneurysmal subarachnoid hemorrhage (aSAH). However, evidence-based treatment strategies are sparse. Since heparin has various effects on neuroinflammation, microthromboembolism and vasomotor function, our objective was to determine whether heparin can be used as a multitarget prophylactic agent to ameliorate morbidity in SAH. Methods: Between June 1999 and December 2014, 718 patients received endovascular treatment after rupture of an intracranial aneurysm at our institution; 197 of them were treated with continuous unfractionated heparin in therapeutic dosages after the endovascular procedure. We performed a matched pair analysis to evaluate the effect of heparin on cerebral vasospasm (CVS), cerebral infarction (CI), and outcome. Results: The rate of severe CVS was significantly reduced in the heparin group compared with the control group (14.2% vs 25.4%; p=0.005). CI and multiple ischemic lesions were less often present in patients with heparin treatment. These effects were enhanced if patients were treated with heparin for >48 hours, but the difference was not significant. Favorable outcome at 6-month follow-up was achieved in 69% in the heparin group and in 65% in the control group. Conclusions: Patients receiving unfractionated continuous heparin after endovascular aneurysm occlusion have a significant reduction in the rate of severe CVS, have CI less often, and tend to have a favorable outcome more often. Our findings support the potential beneficial effects of heparin as a multitarget therapy in patients with SAH, resulting in an additional 'H' therapy in vasospasm treatment.